Roars from the Mountain Colonial Management of the 1951 Volcanic disaster at Mount Lamington - Johnson, R. Wally (ANU Press, 2020)
"Mount Lamington broke out in violent eruption on 21 January 1951, killing thousands of Orokaiva people, devastating villages and destroying infrastructure. Generations of Orokaiva people had lived on the rich volcanic soils of Mount Lamington, apparently unaware of the deadly volcanic threat that lay dormant beneath them. Also unaware were the Europeans who administered the Territory of Papua and New Guinea at the time of the eruption, and who were uncertain about how to interpret the increasing volcanic unrest on the mountain in the preceding days of the disaster. Roars from the Mountain seeks to address why so many people died at Mount Lamington by examining the large amount of published and unpublished records that are available on the 1951 disaster. The information sources also include the results of interviews with survivors and with people who were part of the relief, recovery and remembrance phases of what can still be regarded as one of Australia's greatest natural-hazard disasters."